2001
DOI: 10.1021/jp011447c
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Study of the Reactions of OH-with Chlorinated Methanes. 1. Benchmark Studies of the Gas-Phase Reactions

Abstract: Ab initio electronic structure calculations and variational transition state theory are used to calculate reaction energetics and rate constants for the gas-phase reactions of OH- with CH(4 - n )Cl n for n = 1−4. Two reaction pathways are considered, second-order (bimolecular) nucleophilic substitution (SN2), and proton transfer. Benchmark electronic structure calculations using CCSD(T) and basis sets as large as aug-cc-pVQZ are performed to obtain highly accurate estimates of the enthalpies of reaction. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 29 publications
5
39
0
Order By: Relevance
“…Tables S1–S3 in the supporting information contain the CCSD(T) benchmark data for the energy profiles of the reactions in the three sets of reference data (A, B, and C, see Table 1) taken from the literature 13, 15, 55–75. Each of the original articles are referred to by the letter of the reference set plus a number, e.g., A1 for Ref 55.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tables S1–S3 in the supporting information contain the CCSD(T) benchmark data for the energy profiles of the reactions in the three sets of reference data (A, B, and C, see Table 1) taken from the literature 13, 15, 55–75. Each of the original articles are referred to by the letter of the reference set plus a number, e.g., A1 for Ref 55.…”
Section: Resultsmentioning
confidence: 99%
“…We have evaluated the performance of 50 popular (and less popular) density functionals, covering LDA, GGA, meta‐GGA, and hybrid DFT, for describing a broad spectrum of 64 S N 2 reactions, by comparing the DFT results with highly correlated ab initio benchmark data (mainly CCSD(T)) from the literature13, 15, 55–75 for PES and geometries of stationary points.…”
Section: Discussionmentioning
confidence: 99%
“…where β =1/k B T and Q(T) is the reactant partition function: : A central aspect of the VTST approach involves an assumed separation between the conserved modes, which correspond to vibrations of the separated molecules, and the remaining modes, referred to as the transitional modes, which gradually transform their character throughout the transition state region as the rotations of the separated reactants couple together to form bending and torsional vibrations, and overall rotations in the adduct [96].] With VTST the position of the transition state is varied until the maximum value of the Gibbs free activation energy (∆G † ) is found for reactions in the gas phase and at gas surface interfaces [83,86,88,89,97], which is equivalent to identifying the dynamical bottleneck where the kinetic rate constant is a minimum [98]. [TO DELETE: This procedure is consistent with the consideration that, since re-crossings of molecular dynamical trajectories from the products to the reactants regions are not accounted for at the level of the critical surface separating these two regions in phase space, RRKM rate constants (and thus TST rate constants in the high-pressure limit) represent upper bounds to the exact kinetic rate constants.…”
Section: Computational Detailsmentioning
confidence: 99%
“…The variational TST procedure minimizes thus the re-crossing effects at the dividing critical surface, and gives therefore much more accurate results for rate constants, which can be regarded as benchmark results in the highpressure limit.] The VTST expression for the rate constant is of the form [98]:…”
Section: Computational Detailsmentioning
confidence: 99%
“…On the other hand, in solution the energy profile turns basically into a unimodal reaction [1,2,3,4,5,6,7,8,9,10,11,12] (see Figure 1), accompanied by a significant increase of the reaction barrier. In previous studies [13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42] it was shown that coupled cluster methods in general give accurate results for the energy profile of S N 2 reactions, while density functional methods give qualitatively correct results but often underestimate barriers [15]. This has led to the design of new and improved density functionals (SSB-D [43], S12g [44] and S12h [44]), where in particular the latter hybrid functional (S12h) was shown to provide accurate results for the complete energy profile of S N 2 reactions.…”
Section: Introductionmentioning
confidence: 99%